(untitled) (Journal of Hama University, 2020)
The black and white Ballade chicken feathers were cared in cages in a coop of the open model. The results indicate that the age of sexual maturity of black feathers chicken was no significantly. It has reached 10 days compared to the white feather chickens, and showed the chickens black feather during the production of eggs, ranging from 21 to 37 weeks, the average daily production of eggs by 0.01 eggs per day per hen (no significant), and a statistically significant increase in the average egg weight of the hen with a feather-black where the difference was estimated with an average egg weight of 3.2 g, While the consumption of feed per hen increased black feather color significantly by 8 g / day, which resulted in a significant increase in the amount of feed consumption to produce a kilogram of eggs by 560 g, The mass of eggs produced by black birds was significantly increased by 0.5 kg compared to white feathers. There is significant difference in estimating the coefficient of the shape of the egg, where the coefficient of shape in the Hen black feather by 1.5. Percentage of eggs perforated through the hen’s fingernail increased of Black feathers chickens, with a difference of 2.9%.